The Role of Nix-Mediated Mitophagy in Muscle Stem Cell Fate Decision and Muscle Regeneration - Racine, Jérémy (Université d'Ottawa / University of Ottawa, 2024)
Skeletal muscle is among the tissues displaying the greatest plasticity, attributable to a population of muscle stem cells (MuSCs). At basal conditions, MuSCs are in a standby state called quiescence. Once activated, they can either self-renew or commit toward myogenesis. This balance is required to mount an adequate repair response while maintaining long-term regenerative capacity. In this regard, mitochondria have emerged as important hubs for integrating signals and regulating stem cell behaviour. Mitophagy regulates mitochondrial properties through the autophagic degradation of organelles, suggesting an importance in MuSCs fate. Transcriptomic analysis of quiescent and activated MuSCs highlighted the Nix mitophagy pathway as a key player in quiescence maintenance. Nix is an important ubiquitin-independent mitophagy pathway in stem cell regulation. To test the role of Nix in MuSCs fate decision and muscle regeneration, we developed a conditional knock-out mouse model of Nix specific to MuSCs. First, we reveal that deleting Nix in vivo caused a significant decrease in mitophagy levels in quiescent and early-activated MuSCs. Next, using in vitro studies of culturing single myofibers, we show that Nix deletion alters MuSC fate decisions by causing premature and increased activation and commitment while depleting the MuSC pool. In vivo injury experiments further validate these observations, showing decreased self-renewal capacity post-muscle repair. We propose that dysregulation of Nix-mediated mitophagy disrupts MuSC fate and lineage progression, ultimately leading to muscle impairment. This study sheds light on the intricate interplay between mitophagy and MuSC behaviour, offering insights into potential therapeutic strategies for muscle regeneration.
Keywords: Muscle stem cells; Mitophagy; BNIP3L/NIX; Muscle regeneration; Myogenesis